The transcription factor encyclopedia. - Yusuf, D; Butland, S; Swanson, M; Bolotin, E; Ticoll, A; Cheung, W; Zhang, X; Dickman, C; Fulton, D; Lim, J; Schnabl, J; Ramos, O; et al. (BioMed Central, 2012)
Here we present the Transcription Factor Encyclopedia (TFe), a new web-based compendium of mini review articles on transcription factors (TFs) that is founded on the principles of open access and collaboration. Our consortium of over 100 researchers has collectively contributed over 130 mini review articles on pertinent human, mouse and rat TFs. Notable features of the TFe website include a high-quality PDF generator and web API for programmatic data retrieval. TFe aims to rapidly educate scientists about the TFs they encounter through the delivery of succinct summaries written and vetted by experts in the field. TFe is available at http://www.cisreg.ca/tfe.